2010
DOI: 10.1016/j.ejcts.2009.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Does induction treatment increase the risk of morbidity and mortality after pneumonectomy? A multicentre case-matched analysis☆

Abstract: Current regimens of induction treatment do not seem to increase the risk of morbidity, early mortality and late mortality after pneumonectomy in properly selected patients. This study warrants confirmation from future multicentre prospective randomised trials powered on early outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…However, some reports have shown that induction chemoradiotherapy does not increase the risk of morbidity and mortality after a pneumonectomy in properly selected patients. 3,15) In the present study, there was no significant difference for 90-day mortality and overall survival between patients who underwent a pneumonectomy and those who received a lobectomy, whereas cardiopulmonary morbidity and early mortality rates were greater in patients with a pneumonectomy than those with a lobectomy. Notably, a right pneumonectomy after chemoradiotherapy has been reported to be associated with relatively increased risk and should be performed only in selected patients.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, some reports have shown that induction chemoradiotherapy does not increase the risk of morbidity and mortality after a pneumonectomy in properly selected patients. 3,15) In the present study, there was no significant difference for 90-day mortality and overall survival between patients who underwent a pneumonectomy and those who received a lobectomy, whereas cardiopulmonary morbidity and early mortality rates were greater in patients with a pneumonectomy than those with a lobectomy. Notably, a right pneumonectomy after chemoradiotherapy has been reported to be associated with relatively increased risk and should be performed only in selected patients.…”
Section: Discussionmentioning
confidence: 55%
“…Albain and colleagues recently reported significantly higher mortality rates with a pneumonectomy (26%) as compared to a lobectomy (1%); thus no survival difference was found between the surgical and non-surgical arms in their study, 15) because the increased mortality in patients who required a pneumonectomy after induction chemoradiotherapy adversely affected the overall survival of the surgical group. However, some reports have shown that induction chemoradiotherapy does not increase the risk of morbidity and mortality after a pneumonectomy in properly selected patients.…”
Section: Discussionmentioning
confidence: 84%
“…Asian patients provided 77.2% of the enrolled samples (11 510/14 912) (23,30,31,34,35,40,42,45,46,49,50), including 6923 cases from China (31,35), 4347 cases from Japan (23,30,34,40,42,49,50), 177 cases from Turkey (45) and 63 cases from Korea (46). The other 3402 patients (3402/14 912, ratio = 22.8%) were from European and North American countries and reported in 19 studies (21,22,(24)(25)(26)(27)(28)(29)32,33,(36)(37)(38)(39)41,43,44,47,48). Postoperative BPF was diagnosed in 354 patients by endoscopic inspection and clinical manifestation.…”
Section: The Basic Characteristics Of Included Studiesmentioning
confidence: 99%
“…Authors like Boer, Sunsucke, Roberts, Albain, Venuta, say that in group with preoperative neoadjuvant chemotherapy there were register larger amount of complications, in some series they were statistically significant, and also in some series were detected larger amount of postoperative deaths [3][4][5][6][7]. On other hand authors like Siegenthaler, Perrot, Refai in their evaluations said that there were not significant complications in the group with neoadjuvant hemiotheraphy [8][9][10].…”
Section: Discusionmentioning
confidence: 93%
“…Pre-operative (neo-adjuvant) chemotherapy has shown promise in small trials restricted to stage IIIA patients [3][4][5]. In last time there were many studys to use neoadjuvant hemiotheraphy for IB, IIA and IIB stage also [6][7][8][9][10][11][12]. Many trials have shown that preoperative chemotherapy for lung cancer is feasible but associated with postoperative morbidity and mortality [3,11].…”
Section: Discusionmentioning
confidence: 99%